2001
DOI: 10.1051/0004-6361:20010273
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of highly buoyant thermals in a stratified layer

Abstract: Abstract. The buoyant rise of thermals (i.e. bubbles of enhanced entropy, but initially in pressure equilibrium) is investigated numerically in three dimensions for the case of an adiabatically stratified layer covering 6-9 pressure scale heights. It is found that these bubbles can travel to large heights before being braked by the excess pressure that builds up in order to drive the gas sideways in the head of the bubble. Until this happens, the momentum of the bubble grows as described by the time-integrated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Such a deceleration may cause the thermals to move so slowly they would diffuse away their entropy perturbation before reaching the bottom of the solar convection zone. Brandenburg & Hazlehurst (2001) found that hot, buoyant thermals in stratified domains behave qualitatively similar to Boussinesq thermals. However, we are not aware of past work which carefully examines the effects of stratification on negatively buoyant thermals.…”
Section: Introductionmentioning
confidence: 78%
“…Such a deceleration may cause the thermals to move so slowly they would diffuse away their entropy perturbation before reaching the bottom of the solar convection zone. Brandenburg & Hazlehurst (2001) found that hot, buoyant thermals in stratified domains behave qualitatively similar to Boussinesq thermals. However, we are not aware of past work which carefully examines the effects of stratification on negatively buoyant thermals.…”
Section: Introductionmentioning
confidence: 78%
“…In addition, several papers have addressed the detectability in radio and X-rays of cluster bubbles, including Churazov et al (2001), , Ensslin and Heinz (2002), and Soker et al (2002). Finally, bubbles in stratified atmospheres have been studied in the context of contact binary stars by Brandenburg and Hazlehurst (2001).…”
Section: Introductionmentioning
confidence: 99%
“…The idea that buoyancy plays an important role in the evolution of the radio lobes in galaxies has been first proposed by Gull & Northover (1973) and has been used to estimate the lifetime of the radio lobes in M87 by Böhringer et al (1995). Three-dimensional simulations of hot bubbles in a stratified atmosphere have also been presented by Brandenburg & Hazlehurst (2001).…”
Section: Introductionmentioning
confidence: 99%